Strategic Direction of Corporate Community Involvement - Liu, Gordon; Eng, Teck Yong; Ko, Wai Wai (2013)
Previous research on corporate community involvement (CCI) initiatives indicates that such behaviour is critical for building neighbourhood relationships and extending corporate influence in the community, but there is little theoretical work that provides a clear picture of managing the nature of the initiatives from different stakeholder management approaches. Drawing from theoretical insights of stakeholder theory and the concept of social capital, this article proposes nine strategic directions for CCI initiatives, and concludes by discussing the management implications of the proposed strategic directions. Our proposed approaches have the potential to improve current understanding and practice of corporations and their CCI initiatives.
Keywords: Community; Social Network; Social Capital; Stakeholder Theory; Corporate Social Responsibility